Parallel processor implementation in computerized tomography using transputers : a thesis presented in partial fulfilment of the requirement for the degree of Master of Technology in Production Technology at Massey University - Wu, Wenju (Massey University, 1993)
Image reconstruction by computerized tomography provides a nonintrusive method of imaging the internal structure of objects. From measurements of radiation (e.g. X-rays or gamma rays) passed through an object, it is possible to observe the internal structure. The reconstruction process is computationally intensive and requires imaginative parallel processing algorithms to attain 'real time' performance. The Inmos transputer makes parallel processing algorithms both feasible and relatively straight forward. In this thesis, a modification to the backprojection algorithm is introduced in order to improve the speed of the implementation. Work carried out has involved evaluating how these algorithms ( convolution, backprojection and interpolation ) can be used in multiprocessor concurrent architecture to obtain rapid image reconstruction. Several suitable transputer network structures have been advanced to simulate the image reconstruction. The reconstruction time is decreased very greatly and the image reconstruction result is good.
Keywords: Image processing; Transputers; Parallel processing (Electronic computers); Tomography